Preliminary Study of Right Ventricular Dyssynchrony Under High-Altitude Exposure: Determinants and Impacts - Yang, Yuanqi; Liu, Chuan; Tian, Jingdu; Ding, Xiaohan; Yu, Shiyong; Bian, Shizhu; Yang, Jie; Qin, Zhexue; Zhang, Jihang; Ke, Jingbin; Yuan, Fangzhengyuan; Zhang, Chen; et al. (Frontiers in Physiology, 2020)
The aims of this study were to explore the effect of high-altitude (HA) exposure on the incidence, determinants and impacts of right ventricular dyssynchrony (RVD). In our study, 108 healthy young men were enrolled, and physiological and echocardiographic variables were recorded at both sea level and 4100 m. By using 2-dimensional speckle-tracking echocardiography, RVD was evaluated by calculating the R-R interval-corrected standard deviation of the time-to-peak systolic strain for the 4 mid-basal RV segments (RVSD4) and defined by RVSD4 >18.7 ms. After HA exposure, RVSD4 was significantly increased, and the incidence of RVD was approximately 32.4%. Subjects with RVD showed lower oxygen saturation (SaO2) and RV global longitudinal strain and higher systolic pulmonary artery pressure than those without RVD. Moreover, myocardial acceleration during isovolumic contraction was increased in all subjects and those without RVD but not in those with RVD. Multivariate logistic regression revealed that SaO2 is an independent determinant of RVD at HA (odds ratio: 0.72, 95% CI: 0.56-0.92; P = 0.009). However, the mean pulmonary artery pressure was linearly correlated with the magnitude of RVD in the presence of Notch. No changes were found in RV fractional area change, tricuspid annular motion or tricuspid s’ velocity between subjects with and without RVD. Collectively, we demonstrated for the first time that HA exposure could induce RVD in healthy subjects, which may be mainly attributed to the decline in SaO2 as well as RV overload; the incidence of RVD was associated with reduced RV regional function and blunted myocardial acceleration.